First Case of Transulnar Approach for Angiogram (Coronary and Peripheral) in BSMMU - Ahsan, Syed Ali; Hossain, Ahmed Shafiqul; Rahman, Md Hafizur; Mahmud, Monjur; Siddique, Md Abu; Hossain, Muhmmad Mobarock (University Heart Journal, 2012)
Transfemoral approach is mostly used for coronary and peripheral angiography and intervention. Transradial coronary angiography and intervention has become a popular technique due to reduced local and bleeding complications, easier post-procedural care and patient preference. In certain patients, transradial access may not be possible due to various anatomical reasons and usually, the transfemoral route is used for these patients. In a minority of patients, such as those with significant peripheral arterial disease or obesity, the transfemoral approach is challenging and is associated with an increased risk of local complications or bleeding. Transulnar arterial access, however, has recently been shown to be feasible and safe for both coronary angiography and intervention. The procedural success, advantages and complication rates for this procedure appear similar to those for the transradial approach. This is a case of transulnar artery percutaneous coronary and peripheral intervention in a patient of chronic stable angina and peripheral vascular disease. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11672 University Heart Journal Vol. 8, No. 1, January 2012